Impact of COVID-19 on rehabilitation experiences of physiotherapists - Kaya Ciddi, Pınar; Aras Bayram, Gülay (IOS Press, 2022)
BACKGROUND: As the COVID-19 pandemic progressed, pressures on almost all health sectors in many countries increased, and physiotherapy interventions were canceled for various reasons. OBJECTIVES: The aim of this study was to determine the status of physiotherapists who interrupted their services due to the pandemic and investigate procedures adopted by physiotherapists during face-to-face practice. METHOD: The measuring tool was an online survey administered via Google Forms between January 27 and February 27, 2021. In this descriptive cross-sectional study, the sample consisted of 558 physiotherapists, questions about their clinical experience during the pandemic were answered, and descriptive statistics were examined. RESULTS: Of the physiotherapists, 351 (62.9%) suspended their services due to pandemic, while 207 (37%) of all participants worked without suspending their services since the beginning of the process. Among participants, 303 (54.3%) needed education to use telerehabilitation methods, and 315 (56.5%) monitored their patients with remote communication methods. Handwashing (86.6%), disinfectant (85.3%), gloves (76.5%) and masks (86.6%) were the most common protective measures. CONCLUSIONS: Most physiotherapists had their face-to-face practice interrupted for a short time due to the COVID-19 outbreak, but they continue to treat all disease conditions in spite of inherent physical intimacy and increased risk of infection.
Keywords: Coronavirus; COVID-19; Health Professionals; Preventive Measures; Telehealth